The natural history of substance use disorders. Issue 4 (July 2016) - Sarvet, Aaron L.; Hasin, Deborah
Abstract : Purpose of review: Illicit drugs, alcohol, and tobacco use disorders contribute substantially to the global burden of disease. Knowledge about the major elements of the natural history of substance use disorders (incidence, remission, persistence, and relapse) is crucial to a broader understanding of the course and outcomes of substance use disorders. Recent findings: Prospective cohort studies in nonclinical samples indicate that externalizing psychopathology in earlier life, including early disordered substance use, delinquency, and personality disorders, are related to substance use disorders later in life and chronic course. Externalizing psychopathology may be initiated by early adverse experiences, for example, childhood maltreatment and stressful life events. After controlling for confounders, 'age at first use' as a causal factor for alcohol use disorder later in life and the 'drug substitution' hypothesis are not supported in general population data. Summary: Future research should focus on elaborating the causal framework that leads to the development and persistence of severe substance use disorders, with an emphasis on identifying modifiable factors for intervention by policy makers or health professionals. More research is needed on the natural history of substance use disorders in low-income and middle-income countries.